Model controllingu kosztów - Rubik, Jolanta (The model of cost controlling, 2006)
The model of cost controlling is a kind of norm of carrying out a process of cost controlling implementation in a company. The model has functional and instrumental character, which means that functions of cost controlling are set. These functions are treated as stages of cost controlling system organisation and ways of its realization in the shape of appropriate instruments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 89-95